The Digitalization of Islamic Banking: Public Response to Mobile Banking in Mendahara Ilir - Sapriandi; Daud; Devi, Erwina Kartika; Dewi, Hasna; Saputra, Ahmad Edi (Journal of Economics and Social Sciences (JESS), 2025)
This study aims to analyze the interest of the community in Kelurahan Mendahara Ilir in using Sharia-based mobile banking services, as well as the factors influencing it. In the digital era, Sharia mobile banking serves as a modern financial solution aligned with Islamic principles; however, its adoption rate remains low in this region. Using a descriptive qualitative approach, data were collected through observations, in-depth interviews, and documentation. The findings indicate that the main barriers to using Sharia mobile banking include low digital literacy, limited internet access, and concerns about service security. Internal factors such as technological understanding and religious motivation, along with external factors like social support and education from financial institutions, also influence community interest. The study recommends the implementation of contextual, collaborative, and sustainable educational strategies to enhance the adoption of Sharia financial technology and promote financial inclusion in coastal areas